Natural history of pregnancy‐related enhanced myometrial vascularity following miscarriage. (1st May 2020) - Grewal, K.; Al‐Memar, M.; Fourie, H.; Stalder, C.; Timmerman, D.; Bourne, T.
ABSTRACT: Objectives: Our primary aim was to report the incidence of enhanced myometrial vascularity (EMV) in consecutive women attending our early pregnancy assessment unit, following first‐trimester miscarriage. We aimed further to evaluate the clinical presentation and complications associated with expectant and surgical management of EMV in these women. Methods: This was a prospective cohort study conducted in a London teaching hospital between June 2015 and June 2018, including consecutive patients with an observation of EMV on transvaginal ultrasonography following first‐trimester miscarriage. The diagnosis was made following the subjective identification of EMV using color Doppler ultrasonography and a peak systolic velocity (PSV) ≥ 20 cm/s within the collection of vessels. Women were followed up with repeat scans every 14 days. Management was expectant unless intervention was indicated because of excessive or prolonged bleeding, persistent presence of retained tissue in the endometrial cavity or patient choice. The final clinical outcome was recorded. Time to resolution of EMV was defined as the interval from detection of EMV until resolution. Results: During the study period, there were 2627 first‐trimester fetal losses in the department and, of these, 40 patients were diagnosed with EMV, hence the incidence of EMV following miscarriage was 1.52%. All cases were associated with ultrasound evidence of retained products of conception (RPOC) at presentation (mean dimensions, 22 × 20 × 20 mm). Thirty‐one patients opted initially for expectant management, of which 18 had successful resolution without intervention, five were lost to follow‐up and eight subsequently had surgical evacuation due to patient choice. No expectantly managed case required emergency intervention. Nine patients chose surgical evacuation as primary treatment. No significant correlation was seen between PSV within the EMV at presentation and blood loss at surgery. Median PSV was 47 (range, 20–148) cm/s. The estimated blood loss in all cases managed surgically ranged from 20–300 mL. Presence of RPOC was confirmed in all specimens that were sent for analysis following surgery. For cases successfully managed expectantly, the mean time to resolution was 48 (range, 21–84) days. In the nine cases managed surgically from the beginning, the mean time to resolution of EMV was 10.6 (range, 3–29) days. Conclusions: This study suggests that EMV is an uncommon finding following miscarriage and is associated with the presence of RPOC. Expectant management was a safe option in our cohort, with minimal bleeding, although it was associated with protracted time to resolution. In patients who opted for surgery, the maximum blood loss was 300 mL and no patient required blood transfusion or embolization. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.